2013
DOI: 10.1016/j.biombioe.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Minimal descriptors for characterization and evaluation of Jatropha curcas L. germplasm for utilization in crop improvement

Abstract: Jatropha curcas germplasm collected from peninsular region of India as well as germplasm augmented from various parts of the country was characterized for various agromorphological traits at 3 locations for 3 years. Variability was evident for 38 traits which included both qualitative and quantitative traits. Important yield influencing traits such as plant canopy, branching habit, number of primary branches, peduncle branching, peduncle length, inflorescence compactness, flower ratio, inflorescence abundance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 4 publications
2
23
0
2
Order By: Relevance
“…Other branching patterns are possible due to the high phenotypic plasticity. Sunil et al (2013) observed several branching habits and patterns between different germplasm in a monoculture planting at 2 m 9 2 m, with no pruning, and receiving similar management treatments. Although aboveground phenotypes show a wide range of plasticity, genetic diversity is narrow (Divakara et al 2010).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Other branching patterns are possible due to the high phenotypic plasticity. Sunil et al (2013) observed several branching habits and patterns between different germplasm in a monoculture planting at 2 m 9 2 m, with no pruning, and receiving similar management treatments. Although aboveground phenotypes show a wide range of plasticity, genetic diversity is narrow (Divakara et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Foresters consider jatropha a crop or a plantation crop at best, while agronomists consider it a tree. The disagreement occurs because jatropha has a range of phenotypes; shrub-like, multi-stemmed growth habits with height \5 m, and tree-like, single-stemmed growth habits with height [5 m (Sunil et al 2013). This problem is not restricted to jatropha as Scheffer et al (2014) found that 9.2 % of the tree species assessed were classified as shrubs in the TRY (plant traits) database.…”
Section: Introductionmentioning
confidence: 99%
“…Esses caracteres têm sido sugeridos como descritores para a caracterização e avaliação de genótipos de pinhão-manso (Sunil, 2013). Além desses, a produção de sementes, a altura de plantas, o diâmetro de caule, o número de ramos, o número de flores femininas por racemo floral, o diâmetro de copa também são caracteres relevantes para os programas de melhoramento da espécie.…”
Section: Introductionunclassified
“…The germplasm morphologically established in characterization and pre-evaluation according to Sunil et al (2010 and2013). The comparison of four species conducted into eleven quantitative traits, as well as to twelve qualitative attributes as shown in Tables 2 and 3.…”
Section: Morphological Attributesmentioning
confidence: 99%